Patterns of trophic resource use and individual specialization in two species of darters (Etheostoma: Percidae) - Hopper, Garrett W.; Tobler, Michael (My University, 2017)
Background: Species are often grouped into distinct trophic guilds based on their average diets. But the diets of populations may be highly variable through space and time. Even populations that are described as foraging on a wide variety of dietary resources are often comprised of individuals with very narrow dietary preferences, and such individual specialization may vary among populations as a function of local conditions. River gradients provide subtle variation in environmental conditions, so that stream fishes that occur along such gradients may be studied to reveal how environmental conditions shape trophic resource use and individual specialization. Questions: How does trophic resource use vary among species and populations? Does it correlate with local resource availability? What variability exists in individual dietary widths among populations and species? May we attribute variation in individual dietary widths among sites to any environmental variation? Organisms: Two sympatric stream fishes (Etheostoma flabellare and E. spectabile, Percidae) from nine locations in Oklahoma, USA. Methods: We analysed gut contents of the fish. We measured individual dietary width in each of the populations. We also measured resource diversity and densities as well as the number of competitor species. Results: We found significant variation in the diets between species and among populations of the same species. Furthermore, most populations consisted of individuals with narrow dietary width (i.e. high individual dietary specialization). Variation in individual dietary widths in populations of E. flabellare was correlated with invertebrate density and the number of competitor species, and in E. spectabile with the number of invertebrate species and invertebrate density.
Citation: Hopper, G. W., & Tobler, M. (2016). Patterns of trophic resource use and individual specialization in two species of darters (Etheostoma: Percidae). Evolutionary Ecology Research, 17(1), 53-73. Retrieved from <Go to ISI>://WOS:000384803400004
Keywords: Diet Variation; Environmental Variation; Etheostoma Flabellare; Etheostoma Spectabile; Individual Specialization; Trophic Ecology